Enhancing growth performance and health of coloured-broiler chickens with signal grass meal (Brachiaria decumbens) supplementation under tropical conditions - Ong, Yee Lyn; Chung, Eric Lim Teik; Nayan, Nazri; Aziz, Muhamad Faris Ab; Jesse, Faez Firdaus Abdullah; Sazili, Awis Qurni; Dunshea, Frank R. (Elsevier, 2024)
This study examines the impact of signal grass (Brachiaria decumbens) as a phytobiotic supplement on the production performance and health of coloured-broiler chickens reared in tropical environments. A total of 216 day-old Sasso broiler chicks were randomly assigned to six treatment groups with six replications each. All six treatments received the same commercial diets with some adjustments: Treatment 1 (negative control) with only commercial feed, Treatment 2 (positive control) with 100 mg/kg oxytetracycline, Treatment 3, 4, 5, and 6 with 1.25, 2.50, 3.75, and 5.00 g/kg of B. decumbens grass meal, respectively, without antibiotic. Throughout the eight-week study, body weight and feed intake were recorded weekly for each replicate to calculate body weight gain and feed conversion ratio. Additional evaluations included nutrient digestibility, gut histomorphology, cecal microflora population, carcass characteristics, and meat quality. Blood biomarkers and biochemistry were also analysed to evaluate the chickens' health status. Results indicated that broilers supplemented with B. decumbens grass meal, particularly T6 showed significantly (p<0.05) superior growth performance compared to the negative with reduced FCR of 6.8%. Apparent ileal digestibility was also significantly improved in T6, with 22.32% higher CP digestibility. Enhanced gut histomorphology and a healthier cecal microbial population supported improved nutrient absorption and overall gut health, as evidenced by significant increases in the villi-to-crypt ratio and a higher coliform count than the control. Enhanced carcass characteristics, such as higher full gizzard and gastrointestinal tract weights of T6 broilers, further supported improved digestibility. The supplementation also improved meat quality, with blood biomarkers indicating lower stress and inflammation levels comparable to T2. Additionally, the blood biochemistry of T6 broilers suggested hepatoprotective and hypocholesterolemic effects. Therefore, broilers in T6 demonstrated that B. decumbens has significant potential as an effective feed additive to replace antibiotics in the tropical poultry sector due to its phytocompounds profile, including high saponin content.